Value For Money : An Analysis of The Impact of Village Government Performance on Village Financial Management in Subun Bestobe Village - Seran, Marisa S B (Program Pascasarjana Universitas Negeri Makassar, 2021)
The purpose of this research is to find out the Financial Management Performance of the Village Government, especially in Subun Bestobe Village. The research method used is to use quantitative research method with ratio analysis technique using Value For Money (VFM) method, which uses measurement indicators (economical, efficiency, and effectiveness). From the results of the research through the analysis of the performance ratio of the village government in terms of village financial management using the Value For Money method, shows that the ratio of economic level for the last 5 years is in the category of >100%, thus meeting the economic standards of Value For Money. The efficiency rate over the last 5 years is at the standard of >40%, this ratio exceeds the standard ratio provision at its efficiency level. In the case of related financial management to the efficiency ratio of village financial management performance falls into the category of not meeting the standard of efficiency Value For Money. Meanwhile, in the calculation of effectiveness ratio for the last 5 years the performance of village financial management by the Village Government of Subun Bestobe has met the standards so as to show that the Subun Bestobe Village Government has been effective in the management of village finances to the villagers in Subun Bestobe village. In terms of the effectiveness of financial management can increase if the community in the village is satisfied with the performance of good financial management, especially in village development. So that in the future the village can be a superior village, independent and competitive.